CORRECTION OF CHANGES OF THE ORAL CAVITY’S MICROFLORA DEPENDS UPON THE DURATION OF REMOVABLE DENTURES USE - T. Y. Divnych (Український стоматологічний альманах, 2018)
At the present stage of Prosthetic Dentistry treat defects of teeth and dentition, accompanied by the introduction of the mouth dentures a foreign body should be considered taking into account the combined effect on the entire dentition system as prosthesis provides not only preventive, therapeutic, but side effects the surrounding tissues and organs of the mouth, and contributes to the development of pathogenic organisms.